RURALITY AND POPULARITY OF VILLAGE TOURISM RELATION ON SUMENEP VILLAGE TOURISM - INDONESIA - Valdi FIRSTIANTO; Wido Prananing TYAS; Maya DAMAYANTI (Geo Journal of Tourism and Geosites)
Rurality is a measurement to differentiate a rural from an urban; the lower the level of Rurality, the closer it is to urban characteristics, and vice versa. Related to the concept of authenticity in developing rural tourism, the level of Rurality is predicted to influence the popularity of the village in question. The higher the level of Rurality of a village, the more popular rural tourism will be in that village. Therefore, this research aims to determine the relationship between the level of Rurality and the popularity of rural tourism. This research uses a quantitative approach through three stages of analysis. Th e first is to analyze social media sentiments to rank the levels of tourism popularity. The next step is calculating the rurality levels using a scoring method. Finally, this study derived the emerging patterns between Rurality and the popularity of tourist villages by comparing the results of the first and second analyses. The findings reveal seven patterns, indicating that Rurality goes hand in hand with the popularity achieved where famous villages have a high level of Rurality and vice versa.